DESTRUCTIVE FISHERY AND FISHERY SUSTAINABILITY ASSESSING FISHERY SUSTAINABILITY USING A MULTICRITERIA PARTICIPATORY APPROACH : A Case Study of Small Islands in South Sulawesi - Budiati Prasetiamartati; Akhmad Fauzi; Rokhmin Dahuri; Achmad Fahrudin; Hellmuth Lange (JOURNAL OF COASTAL DEVELOPMENT, 2006)
The sustainability in the integrated human and nature systems or social–ecological systems(SES) of reef fishery needs attention, because the livelihood of many coastal communities is dependentupon it. Likewise, coral reef ecosystem is important marine resource as a source of biodiversity, aspawning aggregation for various reef fish and biota. However, coral reef ecosystem in South Sulawesihas been pressured by reef-related fishing activities, which include destructive practices of bomb andpoison fishing.This study assesses the condition of fishery sustainability in five selected small islands situated inTaka Bonerate Marine National Park and Spermonde Archipelago, South Sulawesi. Multi-criteriaanalysis (MCA) is used as a decision-making tool to analyze and evaluate multiple indicators under aparticipatory group decision-making environment (Mendoza and Prabhu 2004). Four variable criteriaof sustainability indicators are included, namely ecological-criterion indicators, economic-criterionindicators, social-criterion indicators, and institutional-criterion indicators. The result of theassessment is analyzed with the state of coral reef and the state of destructive fishery in the area.